Remdesivir Alleviates Acute Kidney Injury by Inhibiting the Activation of NLRP3 Inflammasome - Yin, Liang; Zhao, Haoxin; Zhang, Huiyu; Li, Yi; Dong, Yuhao; Ju, Huijin; Kong, Feng; Zhao, Shengtian (Frontiers in Immunology, 2021)
Acute kidney injury (AKI) is a frequent clinical complication in critically ill patients, and it rapidly develops into renal failure with high morbidity and mortality. However, other than dialysis, no effective therapeutic interventions can offer reliable treatment to limit renal injury and improve survival. Here, we firstly reported that remdesivir (RDV, GS-5734), a broad-spectrum antiviral nucleotide prodrug, alleviated AKI by specifically inhibiting NOD-, LRR-and pyrin domain-containing protein 3 (NLRP3) inflammasome activation in macrophages. Mechanically, RDV effectively suppressed the activities of nuclear transcription factor(NF)-κB, mitogen-activated protein kinase(MAPK), which further led to the reduction of the inflammasome genes of NLRP3 transcription, limiting the activation of NLRP3 inflammasome in vivo and in vitro. RDV also inhibited other pro-inflammatory genes including tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), IL-12, IL-1β and interferon–β (IFN-β), leading to the reduction of inflammatory factors release. Thus, RDV can ameliorate AKI via modulating macrophage inflammasome activation and inflammatory immune responses and may have a therapeutic potential for patients with AKI in clinical application.